Analisis Nilai-Nilai Kearifan Lokal Masyarakat Baduy dalam Novel Baiat Cinta di Tanah Baduy Karya Uten Sutendy dengan Kajian Ekologi Budaya sebagai Bahan Ajar di SMA - Trisnawati, Trisnawati; Saraswati, Saraswati; Adrianti, Fera (GERAM: Gerakan Aktif Menulis, 2023)
The purpose this research is to describe the local wisdom values ​​contained in the novel Baiat Cinta di Tanah Baduy by Uten Sutendy. The research method used in this research is descriptive qualitative. The data sources used in this research are novels by Uten Sutendy as well as relevant theoretical books related to literature and local wisdom values. The research data is in the form of excerpts from sentences contained in the novel Baiat Cinta di Tanah Baduy by Uten Sutendy. The data collection techniques in this research are reading the entire contents of the novel, identifying the local wisdom values ​​contained in the novel, looking for data related to character values, searching for the benefits of the analysis to be used as teaching material and the researcher collects these points to arrive at the stage conclusion. From this analysis, it can be concluded that in the novel Baiat Cinta di Tanah Baduy by Uten Sutendy there is a cultural ecology that focuses on the environment, niche or habitat, resources and energy. In these four approaches there are types of character values, customs or customs, respect. nature, nature conservation, technological limitations, utilization of natural resources, tolerance values, national values, preserving animals and nature, praying to Allah, humans are weak creatures, believing in Allah's destiny, sacrifice, victory, compassion, mutual cooperation, caring. Keywords: Local Wisdom, Baduy Tribe, Cultural Ecology